Exploring Opportunities for Performance Improvement in a Global Climate Model - Costa, Rhuan; Mendes, Celso Luiz (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2019)
The Brazilian Earth System Model (BESM) is a Global Climate Model (GCM) developed by the Brazilian National Institute for Space Research (INPE). The main purpose of a GCM is to simulate Earth’s climate in a decadal or centennial scale. The simulations usually include representations of the main elements of the Earth, such as atmosphere, ocean, ice and land. Since its first release, BESM has provided support materials for contributions to the Intergovernmental Panel on Climate Change (IPCC). This paper evaluates BESM’s performance and explores optimization possibilities, aiming to speed up the model execution. Our study started with a detailed analysis that characterized the performance of BESM executions on hundreds of processors, which served to reveal the major performance bottlenecks. Next, we worked on schemes to mitigate some of those bottlenecks. The changes made so far resulted on performance gains up to a factor of 4 in some cases, when compared to the way it was previously being executed in production. We also describe ongoing work towards additional performance improvements. Despite presenting results only for BESM, our optimization techniques are applicable to other scientific, multi-physics models as well.